Processing of veracity cues: how processing difficulty affects the memory of event description and judgment of confidence - Nicole Antes; Stephan Schwan; Markus Huff (Cognitive Research)
Abstract In today's rapid dissemination of information, discerning truth from falsehood is crucial. We investigated how cues signaling information veracity influence memory accuracy and confidence in coherent narratives. Two studies manipulated perceptual difficulty in distinguishing true-labeled from false-labeled information in event descriptions using font color as a cue. Study 1 (N = 198) revealed that the presence of veracity cues reduces memory accuracy for the event description. Study 2 (N = 248) showed that when differentiating veracity cues became more challenging, false-labeled information was more frequently misidentified and less accurately remembered. Confidence ratings decreased with the presence of veracity cues (Study 1) but resulted in disproportionately high confidence for sentences labeled as false that were confused as true (Study 2). False-labeled information was less retained, yielding initially more accurate event representation. However, once stored, false-labeled information was recalled with confidence as true, leading to a false representation. Therefore, mechanisms such as highlighting the veracity of information within coherent news articles on social media should be used with consideration.